Generalized Anxiety Disorder, Depressive Symptoms, and Sleep Problem During COVID-19 Outbreak in Ethiopia Among Police Officers: A Cross-Sectional Survey - Tsehay, Mekonnen; Necho, Moges; Gelaye, Habtam; Beyene, Abeba; Birkie, Mengesha (Frontiers in Psychology, 2021)
Background: The outbreak of Coronavirus Disease 2019 (COVID-19) has caused serious threats to people’s health and lives in the world. The police officers are bravely fighting on the front lines of the pandemic everywhere in the world. Our study is the first study of psychological response in the police officers of Ethiopia during the unbridled time of the COVID-19 − 19 outbreaks. Methods: A cross-sectional self-administered questionnaire was conducted to the police officers from Dessie town, and the data were collected between June 20 and July10, 2020. A total of 385 questionnaires were filled correctly accounting to 91%. The questionnaires included the demographic information and psychological tools. The patient health questionnaire (PHQ-9), generalized anxiety disorder 7-item scale (GAD-7), Insomnia Severity Index (ISI), and Brief Resilient Coping Scale questionnaire were employed to assess depression, anxiety, sleep and coping status of participants respectively. Result: The prevalence of depression among participants was 28.9%. Of these 19.7% mild, 7.3% moderate, 1.6 moderate-severe, and 0.3% of the police officers had severe depression. The prevalence of general anxiety symptoms of the participants was 30.2%. Of these, 22.1% of the police officers had mild, 2.6% had moderate, and 5.5% had severe anxiety. And also, 13.8% of police officers had sub-threshold insomnia and 2.1% had clinical (moderate-severe) insomnia. The participants of the male gender, being married, high resilient coping score and high social support had associated with lower depression, anxiety, and Insomnia scores than those of female gender, being single or widowed/divorced, low resilient coping score, and low social support respectively. As age increases the score of PHQ-9, GAD-7, and brief resilient coping scores had increased. Conclusion: The police officers have different levels of anxiety and depression during the COVID-19 pandemic in Dessie. We should call for attention to the psychological response of police officers during the pandemic, and provide them with corresponding help.